Non-linear pharmacokinetics of penciclovir in healthy cats after single and multiple oral administration of famciclovir - Qu, Mengke; Ke, Xiao; Zhang, Zhirong; Zhang, Ling (Frontiers in Veterinary Science, 2025)
IntroductionFeline Infectious Rhinobronchitis (FVR) is a common and serious infectious upper respiratory disease. Famciclovir, an antiviral prodrug initially developed for human herpesviruses, demonstrates significant therapeutic efficacy in cats with FVR caused by feline herpesvirus type 1 (FHV-1).MethodsTo determine the pharmacokinetics of famciclovir in healthy cats after single or multiple oral and intravenous administrations—40 cats in 4 different dose groups received famciclovir through a single oral dose, while 10 cats received famciclovir every 12 h for 14 days, and another 10 cats received a single intravenous dose of penciclovir—in three different phases. At the predetermined time points, blood samples were collected through the radial vein of the cat. The blood samples were analyzed by liquid chromatography–tandem mass spectrometry to detect the concentration of penciclovir in cat plasma. The pharmacokinetic parameters of penciclovir were calculated using a noncompartmental model.ResultsAfter a single oral administration in cats, the absorption and exposure of famciclovir tablets also increased with the increase in dose. After multiple oral administrations of famciclovir tablets, the concentration of the drug fluctuated violently in steady state with no accumulation in the body. The absolute bioavailability of the tested cats after single oral administration of 15.625 g, 31.25, 62.5, and 93.75 mg/kg famciclovir tablets was 67.12, 33.94, 26.45, and 18.37%, respectively.DiscussionIn summary, after oral administration in cats, the absorption and exposure of famciclovir tablets showed overall non-linear pharmacokinetic characteristics. This study provides a scientific basis for the clinical dosage and duration of treatment of FVR with famciclovir tablets.